Le monde ouvrier au Québec - Dion, Gérard (Relations industrielles / Industrial Relations, 1973)
This article reviews the retrospective bibliography "Le monde ouvrier au Québec" by André E. LeBlanc et James D. Thwaites.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z